DAMPAK KURS USD DAN PERJANJIAN PERDAGANGAN INDONESIA JAPAN ECONOMIC PARTNERSHIP AGREEMENT (IJEPA) TERHADAP KINERJA EKSPOR ALAS KAKI INDONESIA KE JEPANG - Yoga, I Made Diksa Indra; Setiawina, Nyoman Djinar (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.06.TAHUN.2023, 2023)
Footwear is one of Indonesia's leading export commodities after textiles, electronics, rubber, palm oil and forest products. Japan is one of the main destinations for Indonesian footwear exports. This study aims to analyze the effect of the US Exchange Rate and the Indonesia Trade Agreement Japan Economic Partnership Agreement (IJEPA) on the performance of Indonesian footwear exports to Japan in 1999-2020. This research is a quantitative research with associative type conducted in Indonesia. The data used are secondary data obtained from UN Comtrade and the Central Statistics Agency. Data collection consists of annual reports for the period 1999-2020. The analysis technique in this research is multiple linear regression analysis. The results of the analysis show that the US Exchange Rate and the Indonesia-Japan Economic Partnership Agreement (IJEPA) simultaneously affect the export of Indonesian footwear to Japan. The US exchange rate and the Indonesia-Japan Economic Partnership Agreement (IJEPA) have partially positive and significant impact on Indonesia's footwear exports to Japan. The US exchange rate is a variable that has a dominant influence on Indonesian footwear exports to Japan.